Video Kinematic Analysis of Timed Up and Go Test in Convalescent Stroke Patients - CAI Tongxin; LEI Mincong; ZHOU Yijun; MENG Dianhuai (康复学报)
ObjectiveThe results of the Timed Up and Go test (TUG test) between convalescent stroke patients and healthy controls were observed and compared by video recording , and the total time and sub-phase kinematic characteristics of the TUG test were analyzed to provide a theoretical basis for clinical application.MethodsUsing the convenient sampling method, according to the inclusion and exclusion criteria, a total of 41 convalescent stroke patients were recruited as the patient group (observation group) in the rehabilitation medical centers of three hospitals (including the First Affiliated Hospital of Nanjing Medical University, etc.) from June to September 2022, and 35 healthy people with gender, age, height and weight matched were selected as healthy control group (control group). The TUG test were recorded by cameras for all subjects. VirtualDube 2® software was used to analyze the kinematic characteristics of the recorded video, including the total time and sub-stages parameters (stage 1 standing up, stage 2 forward walking, stage 3 first turning, stage 4 return walking, stage 5 end turning and sitting down);Moreover, the observation group also received 5 times of sit-to-stand test, single leg support time and 10-meter walking test speed.ResultsCompared with the control group, the observation group had a significant increase in the time of total TUG [26.91 (16.52, 35.98) s] and the sub-stages [1.98 (1.13, 2.48), 8.15 (4.21, 13.02), 4.15 (3.84, 5.93), 6.10 (3.08, 9.94), 5.04 (3.82, 7.03) s] (P<0.05), and there were significant differences in the percentage distribution of each sub-stage (P<0.05). There was a significant positive correlation between the five times sit-to-stand time and the time of total TUG test and each sub-stage in the observation group (P<0.01). There was a significant negative correlation between the single leg support time of the hemiplegic side and the time of total TUG test and each sub-stage (P<0.05). There was a significant positive correlation between 10-meter walking test speed and the time of total TUG test and each sub-stage in the observation group (P<0.01).ConclusionThe TUG test video kinematics analysis can be used to accurately analyze the walking characteristics of patients in the convalescent stroke patients, and the corresponding sub-stage time can reflect the lower limb strength, standing balance, walking stability and other function of stroke patients.